USE OF CLOUD COMPUTING IN SMART FARMING - Singh, Harjinder (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In case of agriculture our country has a great potential of development. Broadly speaking cloud computing is nothing but a highly ‘utilitarian’ orientation of IT services where users benefited on a pay-as-you go basis. In smart farming all agricultural data such as soil, weather, research, crop, farmers, agriculture marketing, fertilizer, and pesticide information may now be consolidated in the cloud. According to an analysis performed by McKinsey, if agricultural connectivity is successfully implemented, the industry might add 500 billion to the global gross domestic product by 2030. With close to 7.8 billion people inhabiting this earth and enjoying tasty food, it’s inevitable to consider ways to meet the rising demand. In fact, estimates show the demand for food is expected to increase anywhere between 59% to 98% by 2050, but unfortunately, places to farm are scarce. As a result, agriculture need to be smarter about finding innovative ways to get more out of each piece of land. In modern era of cloud computing technology very helpful for centralized the all agricultural related data bank (Soil-related, weather, Research, Crop, Farmers, Agriculture marketing, fertilizers and pesticide information) in the cloud.